Solution processed polymer-ABX4 perovskite-like microcavities - Lova, Paola (2021)
Thanks to solution processability and broad emission in the visible spectral range, 2D hybrid perovskite-like materials are interesting for the realization of large area and flexible lighting devices. However, the deposition of these materials requires broad-spectrum solvents that can easily dissolve most of the commercial polymers and make perovskites incompatible with flexible photonics. Here, we demonstrated the integration of broadband-emitting (EDBE)PbCl4 (where EDBE = 2,2-(ethylenedioxy)bis(ethylammonium)) thin films with a solution-processed polymer planar microcavities, employing a sacrificial polymer multilayer. This approach allowed for spectral and angular redistribution of the perovskite-like material, photoluminescence, that can pave the way to all-solution-processed and flexible lightning devices that do not require complex and costly fabrication techniques.